Investigation of conducting pins in sphere filled with phase change material for enhancing heat transfer in thermal energy storage - Nasrul Amri, Mohd Amin; Bruno, Frank, Dr.; Belusko, Martin (Trans Tech Publications., 2013)
Link to publisher's homepage at http://www.ttp.net/